Ultrasharp Fano Resonances Based on the Circular Cavity Optimized by a Metallic Nanodisk - Yilin Wang; Shilei Li; Yunyun Zhang; Li Yu (IEEE Photonics Journal)
A compact structure is proposed to achieve double ultrasharp Fano profiles, which comprises with a metal-insulator-metal (MIM) bus waveguide coupled with a circular cavity and groove resonator. Simulation results show that this two sharp Fano profiles both originate from the interference between the circular cavity and the groove resonator. To optimize the Fano profiles, we introduce a metallic nanodisk in the middle of the circular cavity. The peak of the double Fano resonances can be independently tuned within a certain range by changing the radius of the nanodisk. We can utilize these characteristics to design devices with high performance, such as a highly efficient nanosensor with a sensitivity of ∼1450 nm/RIU and a figure of merit (FOM) about ∼3.51 × 10 4 and a switch with an on/off contrast ratio of about 91 dB. Our structures may have promising applications in nanosensors, switches, and slow-light devices.